Identifikasi Pencemaran Air Laut di Pesisir Pantai Sungai Pisang Kota Padang Ditinjau dari Parameter Fisika dan Kimia - Eko Purwanto; Muhammad Rinaldi; Dwi Puryanti (Universitas Andalas, 2024)
This research aims to identify seawater pollution by determining the concentration of heavy metals (Pb, Cd, and Cu), electrical conductivity, total dissolved solids (TDS), total suspended solids (TSS), temperature, and pH in seawater samples from the coast of Sungai. Pisang, Padang City. Heavy metal concentration values were measured using an Atomic Absorption Spectroscopy (AAS), electrical conductivity was measured using a conductivity meter, TDS and TSS were determined using the gravimetric method, temperature was measured using a thermometer, and pH was measured using a pH meter. From the research results, the highest pH value was obtained at 7.8, the highest temperature value was 33 ℃, the highest electrical conductivity value was 163.6 µS/cm and the highest TSS value was 22.6 mg/L. The average values of pH, temperature, electrical conductivity and TSS obtained did not exceed the quality standard limits based on Minister of the Environment Regulation Number 51 of 2004. The highest TDS value obtained was 3821 mg/L and did not exceed the quality standard limits based on Republic of Indonesia Government Regulation Number 82 of 2001. The concentration values of the heavy metals Pb, Cd, and Cu on the coast of the Sungai Pisang did not exceed the quality standard limits based on Minister of Environment Regulation Number 51 of 2004. From the research results it can be concluded that the sea water on the coast of the Sungai Pisang not polluted.